Methylation of FKBP5 and SLC6A4 in Relation to Treatment Response to Mindfulness Based Stress Reduction for Posttraumatic Stress Disorder - Bishop, Jeffrey R.; Lee, Adam M.; Mills, Lauren J.; Thuras, Paul D.; Eum, Seenae; Clancy, Doris; Erbes, Christopher R.; Polusny, Melissa A.; Lamberty, Gregory J.; Lim, Kelvin O. (Frontiers in Psychiatry, 2018)
Mindfulness Based Stress Reduction (MBSR) is an effective non-pharmacologic treatment for veterans with PTSD. Extensive work has identified epigenetic factors related to PTSD disease risk and pathophysiology, but how these factors influence treatment response is unclear. Serotonin signaling and hypothalamic-pituitary-adrenal (HPA) axis functioning may be perturbed in PTSD and are molecular pathways targeted by PTSD treatments. To identify potential biomarkers for treatment response, we utilized genomic DNA isolated from peripheral blood samples from veterans with PTSD who were responders (n=11) or non-responders (n=11) to MBSR as part of a clinical trial. We assessed methylation levels at CpG sites in regions of the serotonin transporter (SLC6A4) previously associated with expression and depression outcomes, as well as the Intron 7 region of the FK506 binding protein 5 (FKBP5) containing known glucocorticoid response elements suggested to regulate FKBP5. Selected subjects were matched across MBSR responder status by baseline symptoms, age, sex, current smoking status, and current antidepressant use. Percent methylation was compared between responders and non-responders at baseline (pre-MBSR treatment). Additionally, percent change in methylation from baseline to post-treatment was compared between responders and non-responders. There was a significant time x responder group interaction for methylation in FKBP5 intron 7 bin 2 (F(1, 19)=7.492, p=0.013) whereby responders had a decrease in methylation and non-responders had an increase in methylation from before to after treatment in this region. Analyses of the three CpG sites within bin 2 revealed a significant time x responder group interaction for CpG_35558513 (F(1, 19)=5.551, p=0.029) which resides in a known glucocorticoid response element (GRE). Decreases in FKBP5 methylation after treatment in responders as compared to increases in non-responders suggest that effective meditation intervention may be associated with stress-related pathways at the molecular level. These preliminary findings suggest that DNA methylation signatures within FKBP5 are potential indicators of response to meditation treatment in PTSD and require validation in larger cohorts..